Effect of TGF-β1 antisense oligodeoxynucleotide on renal function in chronic renal failure rats - Law, C.H.; Kiew, L.V.; Abdullah, N.A.; Abdul Sattar, M.; Abdul Rahman, N.; Khan, A.H.; Johns, E.J. (Maney Publishing, 2008)
AIM: The aim of the present study was to investigate the effectiveness of transforming growth factor (TGF)-beta1 antisense oligodeoxynucleotides (ODN) in ameliorating deteriorated kidney function in rats with puromycin-induced chronic renal failure (CRF). METHODS: Saline, puromycin, puromycin+TGF-beta1 antisense ODN or puromycin+scrambled ODN were administered to unilaterally nephrectomized rats. Renal hemodynamic and excretory measurements were taken in the anaesthetized rats that had undergone surgical procedure. RESULTS: It was observed that in the CRF rats, there was a marked reduction in the renal blood flow (RBF), glomerular filtration rate (GFR), severe proteinuria, and almost 6-fold increased fractional excretion of sodium (FE Na+) as compared to that in the control rats (all P<0.05). It was further observed that in the CRF rats, the treatment with TGF-beta1 antisense, but not scrambled ODN, markedly attenuated the reduction of RBF, GFR, and proteinuria and markedly prevented the increase of the FE Na+ (all P<0.05). In addition, the renal hypertrophy in the CRF group (P<0.05 vs non-renal failure control) was markedly attenuated after treatment with TGF-1 antisense ODN (P<0.05). Focal segmental glomerulosclerosis was evident only in the untreated and scrambled ODN-treated CRF groups. An interesting observation of this study was that in the CRF rats, although there was marked attenuating and preventive effects of the TGF-beta1 antisense ODN on the deteriorated renal functions, the antisense treatment did not cause any marked change in the renal expression of TGF-beta1 at the protein level. CONCLUSION: Collectively, the data obtained suggests that TGF-beta1 antisense ODN possesses beneficial effects in puromycininduced chronic renal failure and that the deterioration in morphology and impaired renal function in this pathological state is in part dependent upon the action of TGF-beta1 within the kidney.